Effects of a competence development intervention on informal learning and work engagement – a randomized controlled trial - Pankkonen, Otto; Moazami Goodarzi, Ali; Vuori, Jukka (Emerald, 2026)
Purpose – The purpose of this study was to investigate the long-term effects of a competence development intervention on mid- and late-career employees’ participation in informal learning activities and their work engagement, and how workplace contextual factors moderate these effects. Design/methodology/approach – A randomized controlled field experiment was conducted in 15 work organizations. A total of 367 participants were randomly assigned into either an intervention (n = 183) or a comparison group (n = 184). Of these, 248 responded to a six-month follow-up questionnaire. The intervention consisted of four 3-h workshops facilitated by trained trainers in the organizations. Findings – The results indicated that the intervention had a significant main effect on employees’ work engagement. Moreover, the beneficial effects of the intervention on increasing the use of informal learning depended on perceived age-equality of opportunities and supervisory support for development in the workplace. Originality/value – This field-experimental study demonstrates how a resource-building group intervention can improve employees’ work engagement and highlights the moderating role of workplace contextual factors in the long-term effects of the intervention on informal learning at work.